A Rare Ovarian Tumor: The Sclerosing Stromal You Do Not Expect-A Case Series in the Adolescent Population and a Literature Review - Maria Chiara Lucchetti; Francesca Diomedi-Camassei; Cinzia Orazi; Alice Tassi (MDPI AG, 2023)
Sclerosing stromal tumor (SST) is a rare ovarian tumor arising from the sex cord-stromal cells that occurs mainly in young adults during the second and third decades of life and rarely in pediatric and adolescent populations. The objective of this study is to report three illustrative cases of SST in young girls who had undergone surgery at our clinic in or after 2009, and to perform a literature review of this rare ovarian tumor. A retrospective chart review of female patients aged <18 years with a diagnosis of SST treated in a tertiary pediatric hospital was performed. Furthermore, a 10-year review of the SST literature was completed. Three cases of SST at our institution were outlined. After reviewing the literature, 18 SST cases were identified. The mean age at diagnosis was 13.4 years, and the reported clinical presentations were abdominal or pelvic pain and menstrual irregularity. Seven patients had abnormal hormone tests or CA-125 levels. In approximately 30% of cases, conservative surgery was performed, preserving residual ovarian tissue. In conclusion, some preoperative findings may help in suggesting the presence of SST. However, definitive diagnosis can only be made by histopathological examination. It is important to consider this tumor because, given its benign behavior, a conservative approach is preferred, particularly in this age group.